Anatomic Relationship of the Pectoralis Major and Minor Muscles: A Cadaveric Study. (February 2014) - Sanchez, Erick R.; Sanchez, Ruston; Moliver, Clayton
Background: Although the anatomy of the individual pectoralis major and minor muscles has been described previously, never before has the anatomic relationship between these muscles been investigated. Objective: The authors identify the anatomic relationship of the costal origins of the pectoralis major and minor muscles. Methods: Bilateral thoracic wall dissection was completed in 102 cadavers. In each dissection, the chest wall soft tissue was removed, and the distance between costal origins of the pectoralis major and the pectoralis minor muscles was measured. Results: In 49 female and 53 male cadavers, 202 pectoralis major muscles were lifted to expose the costal origins of the pectoralis major and minor muscles. Distances between pectoralis major and pectoralis minor muscles were separated into 3 categories: less than 1 cm, between 1 and 3 cm, and greater than 3 cm. Forty-nine (24%) pectoralis muscle dissections displayed a distance of less than 1 cm between costal muscle origins. Eighty-three dissections (41%) showed an intermediate distance of between 1 and 3 cm, while the remaining 70 (35%) were over 3 cm. No significant difference was observed in these percentages with regard to sex. Ten cadavers displayed asymmetry in pectoralis muscle origin distance. Eight specimens displayed shared fibers between pectoralis major and minor muscles. Conclusions: The anatomic relationship between the costal origin of the pectoralis major and minor muscles is highly variable. Understanding this spatial relationship has important implications for cosmetic and reconstructive breast surgery.